Splintering spheres of security: Peter Sloterdijk and the contemporary fortress city - Klauser, Francisco (My University, 2010)
The paper brings together Peter Sloterdijk’s ‘theory of spheres’ with urban studies literature on the forms and effects of the contemporary urban security agenda, in order to investigate the relationships between the material and (atmo)spherical dimensions of the splintering spaces of security in the contemporary fortress city. The paper hence seeks to conceptualise securitisation strategies not only as spatially articulated measures of surveillance and separation but also as sphere-creating forces in their own right. In this view the paper places particular emphasis on Sloterdijk’s conceptualisation of ‘foam’, thus elucidating the contemporary fortress city as a highly fragmented, polyspherical patchwork of more or less hermetically enclosed and purified security spheres. These spheres are bound together by relations of cofragility and reciprocal implications, and are to different degrees oriented towards the more or less economically motivated collection and management of co-isolated individuals.